The rebirth of politics in Russia - Urban, Michael E. 1947- (Cambridge University Press, 1997)
Blending first hand accounts of grassroots politics with an original theory of social relations under communism, this 1997 book seeks to explain one of the seminal events of this century: the rebirth of politics in Russia amid the collapse of the USSR. The authors trace the process from the pre-political period of dissident activity, through perestroika and the appearance of political groups and publications, elections, the formation of political parties and mass movements, counter-revolution and coup d'état, the victory of democratic forces and the organization of a Russian state; to the struggle of power in the post-communist epoch, the violent end of the first republic and the contentious relations engulfing its successor. By focusing on the popular forces which accomplished Russia's political rebirth, rather than the reforms of the Soviet establishment, this book offers an original perspective on this critical period
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1985-1991; Geschichte 1991-1995; Geschichte 1992-1997; Politik; Glasnost; Political participation / Soviet Union; Political culture / Soviet Union; Political participation / Russia (Federation); Political culture / Russia (Federation); Post-communism / Russia (Federation); Politische Beteiligung; Perestroika; Politische Kultur; Sowjetunion; Soviet Union / Politics and government / 1985-1991; Russia (Federation) / Politics and government / 1991-; Russland